Gender and sex bias in clinical trial recruitment in Alzheimer's disease: Findings from Fundació ACE: Intersections of sex/gender and race/ethnicity in cognitive aging and Alzheimer's disease trajectories. (7th December 2020) - Abdelnour, Carla; Valero, Sergi; Rosende‐Roca, Maitee; Lafuente, Asuncion; Hernandez, Isabel; Tartari, Juan Pablo; Santuccione, Antonella; Ferreti, Maria Teresa; Maguire, Peggy; Buendía, Mar; Pancho, Ana; Tarraga, Lluis; et al.
Abstract: Background: FDA has made great efforts to promote inclusion of women in clinical trials. The aim is to protect specific biological gender and sex issues and encourage drug developers to consider specific clinical outcomes and drug‐safety profiles in terms of gender and sex. Alzheimer's disease (AD) affects predominantly women, who double men in the number of patients diagnosed with dementia. Therefore, we explored gender and sex bias in the inclusion criteria for clinical trials in AD. Here our aim was to compare main inclusion criteria for clinical trials in MCI and dementia patients in terms of sex. Method: Patients evaluated at FACE from 1996 to 2019 with CDR 0, 5 to 2 evaluated from 1996 to 2019 were analyzed. Then, we used the main inclusion criteria for AD clinical trials to compare the sample in terms of sex and syndromic diagnosis. The chosen variables were age, sex, education, comorbidities, treatment and MMSE score. Logistic regression analysis was used accounting for these variables. Result: From a total sample of 20, 203 MCI and dementia patients, we selected potential candidates for clinical trials with complete information regarding age, years of education, MMSE, comorbidities and treatment. After adjusting for age, years of education, comorbidities and treatment, in the dementia sample only age and years of education showed statistically significant differences. Whereas in the MCI sample: age, years of education, treatment and comorbidities showed statistically significant differences (Table 1 and 2). Conclusion: Women with MCI and dementia are less likely to participate in a clinical trial due to older age and less years of education than men. Another factor that prevent women for participating in clinical trials is their comorbidities when compared to men, whereas men are excluded due to treatment criteria more often than women. These results show that there is a pre‐selection bias against women in AD clinical trials because of demographic characteristics. Therefore, participation of women in clinical trials does not reflect the prevalence of AD among women and is not representative of reality. Efforts should be made to provide equal opportunities to potential clinical trials candidates regardless of gender.